A Zn–S aqueous primary battery with high energy and flat discharge plateau. Issue 77 (9th September 2021) - Luo, Lian-Wei; Zhang, Chong; Wu, Xianyong; Han, Changzhi; Xu, Yunkai; Ji, Xiulei; Jiang, Jia-Xing
Abstract : A primary battery with a high areal energy of 7.7 mW h cm −2 and a flat discharge plateau at around 0.7 V was developed by employing sulfur, Zn foil and 1 M ZnCl2 aqueous solution as the cathode, anode and electrolyte, respectively. Abstract : We demonstrate a disposable aqueous primary battery chemistry that comprises environmentally benign materials of the sulfur cathode and Zn anode in a 1 M ZnCl2 aqueous electrolyte. The Zn–S battery shows a high energy density of 1083.3 Wh kg −1 for sulphur with a flat discharge voltage plateau around 0.7 V. When operating at a high mass loading of 8.3 mg cm −2 for sulfur in the cathode, the battery exhibits a very high areal capacity of 11.4 mA h cm −2 and areal energy of 7.7 mW h cm −2 .